Influence of instructional strategies on learning achievement through approved business studies textbooks in secondary schools in Nairobi County, Kenya - Bekele, Sarah Getahun; Amollo, Paul Odundo; Mwangi, John Kamau; Ganira, Lilian Khavugwi (Asian Journal of Contemporary Education, 2025)
Whenever learners are engaged through learning activities, enthusiasm is enhanced, leading to increased learning experiences. Conversely, inadequately designed content exposes learners to undesirable experiences, challenging creativity and imagination for self-directed learning. The objectives of this study were to examine the influence of active listening and inclusivity on learning achievement. The study adopts a mixed-methods approach, utilizing the Solomon four-group design, with quantitative data collected from teachers and learners. Data were gathered through structured questionnaires, and descriptive and inferential statistics were employed for analysis. The findings revealed that both active learning approaches and the distinction between theory and practice significantly contribute to learning achievement in secondary schools. Regression analysis indicated that these factors jointly explain 56.9% of the variation in learning achievement (R² = 0.569). Active learning approaches had a significant positive impact on learning achievement (β = 0.584, p = 0.002), suggesting that for each unit improvement in active learning, learning achievement increased by 0.584 units. Hypothesis testing led to the rejection of both H01 and H02, affirming the significant influence of active teaching methods on improving learning achievements. The study concludes that instructional techniques are crucial in enhancing learning outcomes in business studies. Based on these findings, it is recommended that targeted teacher training programs be implemented to promote innovative teaching strategies, alongside regular reviews of textbook content for relevance and accuracy. Furthermore, policymakers should ensure resource allocation for quality instructional materials and professional development to foster an integrated and effective educational system.